(untitled) (Muitas Vozes, 2024)
The tensions between fiction and non-fiction have become more visible in 21st century’s brazilian narratives, allowing for discussion about the factual nature of the events being narrated. Drawing on this debate, we propose a critical-interpretive analysis of Silviano Santiago’s work O falso mentiroso (2004) and its composition as a novel that simulates an autobiography. Specifically, we identify and discuss the contours among the elasticity of contemporary novelistc language, primarily driven by a memorialistic return. We highlight certain references that underpin our discussion: a) the structural definitions of autofiction by Martin (2014), Nogueira (2018) and Santiago (2018); b) contemporary literary theories by Hutcheon (1992), Ginzburg (2012), and Fuks (2016; 2017); c) ideas about the category of memory proposed by Seligmann-Silva (2002) and Sarlo (2007). In the conclusions, we emphasize the condition of a hybrid character in the work, on the verge of a new fiction constructed through the pact of ambiguity in the narration of a subject who, fragmented by trauma, invents their origin through novelict creation.